Innovative dulce de leche made by sheep’s milk with and without the addition of sheep’s milk cream - Ferreira M.B. (2021)
© 2021, Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA. All rights reserved.The objective of this work was to develop innovative formulations of dulce de leche made with sheep’s milk with and without the addition of sheep’s milk cream and evaluate the shelf life of these products. Physicochemical and microbiological evaluations were performed on sheep’s pasteurized milk and cream, as well as on dulce de leche right after production and during the storage time. Addition of cream to sheep dulce de leche did not change the physicochemical and microbiological parameters between formulations. The dulce de leche showed dark color and adequate results of protein, fat, total and microbiological counts (thermotolerant coliforms, Staphylococcus aureus, Salmonella sp. in all evaluations, and total mesophilic aerobic up to 150 days of storage). Innovative formulations of dulce de leche made by sheep’s milk were developed, differentiated from those existing in the Brazilian market, but a specific legislation is required in Brazil focused on the specific characteristics and quality parameters of sheep’s milk and its derivatives.